Acceptability and proof of concept of internet-delivered treatment for depression, anxiety, and stress in university students: protocol for an open feasibility trial. Issue 1 (December 2016) - Frazier, Patricia; Richards, Derek; Mooney, Jacqueline; Hofmann, Stefan; Beidel, Deborah; Palmieri, Patrick; Bonner, Christopher
Abstract Background In recent years, university counseling and mental health services have reported an increase in the number of clients seeking services and in yearly visits. This trend has been observed at many universities, indicating that behavioral and mental health issues pose significant problems for many college students. The aim of this study is to assess the acceptability and proof of concept of internet-delivered treatment for depression, anxiety, and stress for university students. Methods/design The study is an open feasibility trial of the SilverCloud programs for depression (Space from Depression), anxiety (Space from Anxiety), and stress (Space from Stress). All three are 8-module internet-delivered CBT (iCBT) intervention programs. Participants are assigned a supporter who provides weekly feedback on progress and exercises. Participants will complete the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and stress subscale of the Depression, Anxiety, Stress Scale-21 (DASS-21) as the outcome measures for the depression, anxiety, and stress interventions, respectively. Other outcomes include measures of acceptability of, and satisfaction, with the intervention. Data will be collected at baseline, 8 weeks and 3-month follow-up. Discussion It is anticipated that the study will inform the researchers and service personnel of the programs' potential to reduce depression, anxiety, and stress in a student population as well as the protocols to be employed in a future trial. In addition, it will provide insight into students' engagement with the programs, their user experience, and their satisfaction with the online delivery format.